Modeling and Analysis of a Multilevel Parallel Hybrid Active Power Filter - Demirdelen, T.; Kayaalp, R. I.; Tumay, M. (Engineering, Technology & Applied Science Research, 2016)
This paper introduces a new control approach for the Multilevel Parallel Hybrid Active Power Filter (M-PHAPF) which can compensate harmonics and variable reactive power demand of loads by controlling the DC link voltage adaptively in medium voltage applications. By the means of this novel control method, M-PHAPF obtains a better and more efficient performance in the compensation of harmonics and reactive power compared to when using conventional control methods. The performance and stability of the proposed method are verified with a simulation model realized in PSCAD/EMTDC with different case studies. The simulation results demonstrate that harmonic compensation performance meets the requirements of the IEEE-519 standard.